The serine protease Pic as a virulence factor of atypical enteropathogenic Escherichia coli. (3rd March 2016) - Abreu, Afonso G.; Abe, Cecilia M.; Nunes, Kamila O.; Moraes, Claudia T. P.; Chavez-Dueñas, Lucia; Navarro-Garcia, Fernando; Barbosa, Angela S.; Piazza, Roxane M. F.; Elias, Waldir P.
Abstract: Autotransporter proteins (AT) are associated with bacterial virulence attributes. Originally identified in enteroaggregative Escherichia coli (EAEC), Shigella flexneri 2a and uropathogenic E. coli, the serine protease Pic is one of these AT. We have previously detected one atypical enteropathogenic E. coli strain (BA589) carrying the pic gene. In the present study, we characterized the biological activities of Pic produced by BA589 both in vitro and in vivo . Contrarily to other Pic-producers bacteria, pic in BA589 is located on a high molecular weight plasmid. PicBA589 was able to agglutinate rabbit erythrocytes, cleave mucin and degrade complement system molecules. BA589 was able to colonize mice intestines, and an intense mucus production was observed. The BA589Δ pic mutant lost the capacity to colonize as well as the above-mentioned in vitro activities. Thus, Pic represents an additional virulence factor in aEPEC strain BA589, associated with adherence, colonization and evasion from the innate immune system.